2003
DOI: 10.1007/s00405-003-0709-5
|View full text |Cite
|
Sign up to set email alerts
|

Reflux of nasopharyngeal content into middle ear through the eustachian tube

Abstract: Whether nasopharyngeal content passes into the middle ear in patients without any head and neck pathology during the recovery phase of anesthesia is shown with an objective and prospective method. Thirty-eight patients, 21 female and 17 male, aged between 17 and 76, were included in the study. During the recovery phase of general anesthesia, 10 ml of 5 mCi Tc-99m-MAA was administered intranasally to the patients with a 10-F catheter. A manometer-adapted cuffed intubation tube was placed in the nasal passage so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The first group includes conditions and symptoms that are probably associated with GERD: laryngopharyngeal reflux (LPR) disease, dental erosion, chronic cough, bronchial asthma. The second group comprises conditions in the case of which the causative relationship with GERD was not evidently proved, such as sinusitis, pharyngitis, otitis media, and sleep disorders [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The first group includes conditions and symptoms that are probably associated with GERD: laryngopharyngeal reflux (LPR) disease, dental erosion, chronic cough, bronchial asthma. The second group comprises conditions in the case of which the causative relationship with GERD was not evidently proved, such as sinusitis, pharyngitis, otitis media, and sleep disorders [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ayanoglu et al demonstrated reflux of radionuclidemarked nasopharyngeal content into the middle ear via the eustachian tube in one of 38 non-selected patients. 10 However, in our patient the cisternographic findings, as well as the coincidence of osseous defects in the right mastoid roof and unilateral CSF middle-ear effusion on the same side, indicated a temporal bone CSF leak, which appeared to have spontaneously closed by the time of surgery.…”
Section: Discussionmentioning
confidence: 86%
“…The patients were extubated 10 min after the radionuclide was applied. Passage of nasopharyngeal contents into the middle ear was not a statistically significant observation, therefore this study does not support the hypothesis that reflux of nasopharyngeal contents can happen directly through the eustachian tube into the middle ear and cause deleterious effects [1]. Of course, this study involved adults alone.…”
Section: Clinical Studiesmentioning
confidence: 82%